Physico-chemical and biological characterization of urban municipal landfill leachate. (January 2017) - Naveen, B.P.; Mahapatra, Durga Madhab; Sitharam, T.G.; Sivapullaiah, P.V.; Ramachandra, T.V.
Abstract: Unscientific management and ad-hoc approaches in municipal solid waste management have led to a generation of voluminous leachate in urban conglomerates. Quantification, quality assessment, following treatment and management of leachate has become a serious problem worldwide. In this context, the present study investigates the physico-chemical and biological characterization of landfill leachate and nearby water sources and attempts to identify relationships between the key parameters together with understanding the various processes for chemical transformations. The analysis shows an intermediate leachate age (5–10 years) with higher nutrient levels of 10, 000–12, 000 mg/l and ∼2000–3000 mg/l of carbon (COD) and nitrogen (TKN) respectively. Elemental analysis and underlying mechanisms reveal chemical precipitation and co-precipitation as the vital processes in leachate pond systems resulting in accumulation of trace metals. Based on the above criteria the samples were clustered into major groups that showed a clear distinction between leachate and water bodies. The microbial analysis showed bacterial communities correlating with specific factors relevant to redox environments indicating a gradient in nature and abundance of biotic diversity with a change in leachate environment. Finally, the quality and the contamination potential of the samples were evaluated with the help of leachate pollution index (LPI) and water quality index (WQI) analysis. The study helps in understanding the contamination potential of landfill leachate and establishes linkages between microbial communities and physico-chemical parameters for effective management of landfill leachate. Graphical abstract: Highlights: Landfill leachate were medium aged (5-10 years). Heavy metals concentrations indicated predominantly municipal solid waste dumping. Microbiological analysis showed bacilli and substantially varying composition of microflora. LPI values indicates unstable and immature leachate that are still undergoing decomposition. Unusable and poor water quality in water bodies due to ions and nutrient enrichment.